Treino de ouvinte e a relação entre tatos e mandos como protocolo experimental para a aquisição de regras simples - Gamba, Jonas Fernandes (2012)
The analysis of the relation between listener and speaker repertoires has contributed to the comprehension about the processes involved in the acquisition of complex verbal skills. The study of rule-governed behavior is part of these efforts. Further, it has been hypothesized that the transformation effect of verbal rules is dependent on the existing bidirectional relations between words and objects specified in the rule. The present study aimed to analyze how the relation between listener training and the emergence of tacts and mands may be understood as a basis to interpret simple occurrences of rule-construction and rule-following repertoires during acquisition. The basic procedure involved teaching motor signs for known and unknown items through MTS tasks in a specific context (listener training), and testing for the emergence of mands and tacts and the rule-following and rule-construction behavior that required the use of this information in a different context. Participants learned to respond to new signs by selecting the appropriate visual stimuli (pictures of containers, tools, and unfamiliar stimuli). Tacts were tested asking the participant to signalize in the presence of the pictures. On the other hand, mands were tested in a context where the participants were required to signalize the missed tools necessary to use specific containers. Then, 3 unfamiliar stimuli were used to substitute 3 of the stimuli used in the original training. The final tests consisted of to assess if the information learned during the original training could be transfer to the unfamiliar stimuli. Results pointed out to the emergence of tacsts and mands after listener training for most of the participants. However, the transformation effect of verbal rules using unfamiliar stimuli seemed to be related with the existence of bidirectional relations between the signs and objects specified in the rule.